2013
DOI: 10.1136/bmj.f2310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of autologous blood injections in treatment of mid-portion Achilles tendinopathy: double blind randomised controlled trial

Abstract: Objective To assess the effectiveness of two peritendinous autologous blood injections in addition to a standardised eccentric calf strengthening programme in improving pain and function in patients with mid-portion Achilles tendinopathy.Design Single centre, participant and single assessor blinded, parallel group, randomised, controlled trial.Setting Single sports medicine clinic in New Zealand.Participants 53 adults (mean age 49, 53% men) with symptoms of unilateral mid-portion Achilles tendinopathy for at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 45 publications
(85 reference statements)
1
46
0
1
Order By: Relevance
“…The designs of the appraised studies varied slightly, from eccentric strength training in conjunction with ultrasound-guided intratendinous PRPI 1,8 to peritendinous ABI and the standard of care. 2,4 All 4 studies found improvement in VISA-A scores regardless of treatment allocation.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…The designs of the appraised studies varied slightly, from eccentric strength training in conjunction with ultrasound-guided intratendinous PRPI 1,8 to peritendinous ABI and the standard of care. 2,4 All 4 studies found improvement in VISA-A scores regardless of treatment allocation.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
“…1,2 It presents with localized pain, stiffness, and swelling in the midportion of the Achilles tendon. 3 The physical stress placed on the tendon results in microtrauma, which leads to subsequent inflammation and degeneration.…”
Section: Clinical Scenariomentioning
confidence: 99%
See 3 more Smart Citations